(untitled) (Ameghiniana, 2019)
Autobranchia Grammysiidae bivalves from the Silurian and the Devonian beds of Central Andes Basin of Western Gondwana are herein presented. They were collected in nine scattered outcrops in Eastern Cordillera, Western Altiplano, Interandean and Subandean Bolivia. A total of 34 specimens of a good to regular state of preservation were studied. It is the first time that the genera Grammysia and Grammysioidea from the Eifelian and the Givetian of Bolivia are formally described. This is the first record of Andinodesma radicostata from Ludlowian to Pridolian sandstones of the Interandean of Villagranado and Sobo Sobo. It is the first Bolivian record of the cosmopolitan genus Sanguinolites from the Eifelian of Altiplano (Belén) and Subandean (Alarache). In this paper, the oldest record of the endemic species of Pholadella radiata from the Emsian of Western Gondwana (Icla and Sobo Sobo) is reported. It documents the important dispersion of the Grammiisydae Family during the Eifelian and Givetian times in the Central Andes with genera as Grammysioidea, Grammysia, Sanguinolites and Pholadella. This research contributes to the as yet inaccurately known Silurian and Devonian paleogeography of the Central Andes Basin and is an update of very few and old reports and presents new findings of Grammysiidae bivalves from Bolivia. doi: 10.5710/AMGH.15.08.2019.3259